1999
DOI: 10.1055/s-2007-973490
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Viral Load and CD8 T-Lymphocytes with Development of Neurological Manifestations in Vertically HIV-1-Infected Infants. A Prospective Longitudinal Study

Abstract: To assess the predictive power of immunological and virological markers for the development of neurological syndromes, 39 HIV-1-infected infants with a mean age of 4.05+/-0.5 months and without neurological manifestations at enrolment were studied. They had neither been previously treated with antiretroviral therapy, nor had their mothers been given such treatment during pregnancy. They were routinely assessed for signs of neurological impairment during follow-up (19.54+/-3.37 months). Cox regression analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…1 We previously demonstrated in a prospective study that CD8 ϩ T-lymphocyte counts in the first months of life were significantly associated with the risk for emergence of neurologic signs defining probable PE (cognitive deterioration, cerebral atrophy, progressive motor dysfunction, gait disorder, reflex http://www.pediatrics.org/cgi/content/full/111/2/e168 e173 disturbances, abnormal muscle tone, and HIV-1 encephalitis. 15 Of note, there were not differences in confounding factors, particularly equal number of patients exposed to drugs in utero. The most striking result is that among all of the immunologic and virologic variables assessed in this observational study, the only significant difference during the first months of life and before the onset of PE are the CD8 ϩ T-lymphocytes.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…1 We previously demonstrated in a prospective study that CD8 ϩ T-lymphocyte counts in the first months of life were significantly associated with the risk for emergence of neurologic signs defining probable PE (cognitive deterioration, cerebral atrophy, progressive motor dysfunction, gait disorder, reflex http://www.pediatrics.org/cgi/content/full/111/2/e168 e173 disturbances, abnormal muscle tone, and HIV-1 encephalitis. 15 Of note, there were not differences in confounding factors, particularly equal number of patients exposed to drugs in utero. The most striking result is that among all of the immunologic and virologic variables assessed in this observational study, the only significant difference during the first months of life and before the onset of PE are the CD8 ϩ T-lymphocytes.…”
Section: Discussionmentioning
confidence: 92%
“…More important, CD8 ϩ T-lymphocytes were a predictive marker for PE independent of the CD4 ϩ Tlymphocyte and viral load (VL). 15 Here, we sought to determine in an observational study whether any immunologic (CD4 ϩ and CD8 ϩ T-lymphocyte counts, monocyte counts) or virologic (VL, biological characteristics of viral isolates) marker might be predictive of PE and whether any particular marker may be involved in the timing of clinical onset of PE. To evaluate this hypothesis, we initially examined the occurrence of PE in a cohort of vertically HIV-1-infected children.…”
mentioning
confidence: 99%
“…22 Gurbindo et al, on the other hand, reported that both VL and lymphocyte count (CD8 more than CD4) were predictive of progression of neurologic impairment. 23 A Spanish study spanning 1984 to 2000 found that only CD8 level in the first month of life was predictive of progression to PHE. 24 The authors speculated that increased CD8 trafficking through the blood-brain barrier could lead to the development of PHE.…”
Section: Discussionmentioning
confidence: 99%
“…This manifestation has not been reported in young children. The risk of clinical HIV encephalopathy increases with very early age of infection and with high viral loads [Gurbindo et al, 1999]. In vertically transmitted HIV, advanced maternal disease is a risk for encephalopathy in the infant, probably due to high maternal viral loads.…”
Section: Pathophysiologymentioning
confidence: 99%